2021
DOI: 10.1002/jcop.22604
|View full text |Cite|
|
Sign up to set email alerts
|

Combining participatory action research and emerging ways of collective action to promote institutional change toward social commitment: Groundings, strategies, and implications of an experience

Abstract: Aims: This study reports the foundations, strategies, and results of an institutional change experience based on the combination of participatory-action-research and new currents of collective mobilization and political participation. It aimed to achieve the institution's greater social commitment and a more participatory and transparent management. Methods: The process took place in a Spanish public university and was promoted and coordinated by a Work Group that emerged from grassroots university community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This research employed a qualitative approach using data collection methods, including indepth interviews and participant observation (Creswell, 2013;Sugiyono, 2021). The field study applied the participatory action research model (López et al, 2023;Maring, 2022a), which is shown by: First, the researchers used observation and in-depth interview methods to obtain data about the revitalization of sociocultural values. Second, the researchers supervised university students' learning programs at Jabung Village.…”
Section: Methodsmentioning
confidence: 99%
“…This research employed a qualitative approach using data collection methods, including indepth interviews and participant observation (Creswell, 2013;Sugiyono, 2021). The field study applied the participatory action research model (López et al, 2023;Maring, 2022a), which is shown by: First, the researchers used observation and in-depth interview methods to obtain data about the revitalization of sociocultural values. Second, the researchers supervised university students' learning programs at Jabung Village.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have demonstrated that collaborative institutions enhance cooperation levels, while critics argue that actors often engage in discussions without taking tangible actions to address specific environmental issues (Lubell, 2004). In the institutional setting, challenges arise in securing adequate stakeholder participation, thereby hindering democratic and comprehensive collective decision‐making (Lopez et al., 2021).…”
Section: Introductionmentioning
confidence: 99%